Police Squad : the complete series [videorecording (DVD)] - Zucker, David, 1947-; Zucker, Jerry; Abrahams, Jim, 1944-; Nielsen, Leslie, 1926-2010; North, Alan, 1920-2000; Weiss, Robert K.; Wuhl, Robert; Dante, Joe, 1948-; Brown, Georg Stanford (CBS DVD., 2006)
Features the crime-solving adventures of Detective Frank Drebin, a Sergeant Lieutenant Captain of Police Squad, a special division of the police department. Together Drebin and his boss, Captain Ed Hocken, crack the toughest cases in the big city, encountering sight-gags, slapstick, puns, and non-sequiturs along the way.